PENERAPAN MANAJEMEN BERBASIS SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SD NEGERI 62 KOTA BANDA ACEH - Ihsan .; Djailani AR; Sakdiah Ibrahim (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2014)
Abstract: School-based management is school management system that gives the school the authority and power to regulate school in accordance with school’s potential, demand and the need. This research aimed to find out principal’s leadership in improving the quality of education, implementation, and obstacles faced in implementing school-based management. To achieve these objectives, this research employed qualitative approach. Data was collected through interview, observation, and documentation study. The procedures of data analysis were data reduction, data display, and verification. The research subjects were principal, vice-principal, and teachers. The results showed that; (1) principal leadership in improving the quality of education was implemented by adjusting the policy rules and school’s objectives, combining the work system with school’s resources in order to obtain high achievement with a focus on improving the learners’ quality. (2) The implementation of school-based management to achieve education programs was implemented by formulating the socialization stages, vision, mission, school’s objectives, school’s challenges, and SWOT (Strength, Weakness, Opportunities, and Threats) analysis. (3) The obstacles were not arisen in implementing school-based management if it was viewed from staff/employees condition. The teacher condition was not good in discipline and responsibility and the school was not good in government transportation.Keywords: School Based Management, and Quality of Education.Abstrak: Penelitian ini bertujuan untuk mengetahui kepemimpinan kepala sekolah dalam meningkatkan mutu pendidikan, implementasi manajemen berbasis sekolah dalam pencapaian program pendidikan, dan kendala yang dihadapi kepala sekolah dalam menerapkan manajemen berbasis sekolah. Untuk mencapai tujuan tersebut, penelitian ini menggunakan pendekatan kualitatif. Teknik pengumpulan data dilakukan melalui wawancara, observasi, dan studi dokumentasi. Prosedur analisis data adalah reduksi data, display data, dan verifikasi. Sedangkan subjek penelitian adalah kepala sekolah, wakil kepala sekolah, dan guru. Hasil penelitian menunjukkan bahwa: (1) Kepemimpinan kepala sekolah dalam meningkatkan mutu pendidikan dilakukan dengan menyesuaikan aturan kebijakan dan tujuan pokok sekolah, memadukan sistem kerja dengan sumber daya sekolah agar memperoleh prestasi yang tinggi dengan fokus pada pengembangan mutu peserta didik; (2) Implementasi manajemen berbasis sekolah dalam pencapaian program pendidikan dilakukan dengan tahapan sosialisasi, merumuskan visi, misi dan tujuan sekolah, mengidentifikasi tantangan sekolah, dan melakukan Analisis SWOT; dan (3) Kendala yang dihadapi kepala sekolah dalam implementasi manajemen berbasis sekolah tidak memiliki kendala bila dilihat dari kondisi staf/karyawan sekolah, kondisi guru di sekolah masih terkendala dengan kedisiplinan dan tanggungjawab, sedangkan kondisi lingkungan sekolah terkendala dengan ketidaknyamanan kendaraan dan sarana transportasi pemerintah.Kata kunci : Manajemen Berbasis Sekolah, dan Mutu Pendidikan.